On a conjecture of Vukman - Qing Deng (International Journal of Mathematics and Mathematical Sciences)
Let R be a ring A bi-additive symmetric mapping d:R×R→R is called a symmetric bi-derivation if, for any fixed y∈R, the mapping x→D(x,y) is a derivation. The purpose of this paper is to prove the following conjecture of Vukman.